Phase I dose-escalation single centre clinical trial to evaluate the safety of infusion of memory T cells as adoptive therapy in COVID-19 (RELEASE). (September 2021) - Pérez-Martínez, A.; Mora-Rillo, M.; Ferreras, C.; Guerra-García, P.; Pascual-Miguel, B.; Mestre-Durán, C.; Borobia, A.M.; Carcas, A.J.; Queiruga-Parada, J.; García, I.; Sánchez-Zapardiel, E.; Gasior, M.; et al.
Abstract: Background: Effective treatments are still needed to reduce the severity of symptoms, time of hospitalization, and mortality of COVID-19. SARS-CoV-2 specific memory T-lymphocytes obtained from convalescent donors recovered can be used as passive cell immunotherapy. Methods: Between September and November 2020 a phase 1, dose-escalation, single centre clinical trial was conducted to evaluate the safety and feasibility of the infusion of CD45RA − memory T cells containing SARS-CoV-2 specific T cells as adoptive cell therapy against moderate/severe cases of COVID-19. Nine participants with pneumonia and/or lymphopenia and with at least one human leukocyte antigen (HLA) match with the donor were infused. The first three subjects received the lowest dose (1 × 10 5 cells/kg), the next three received the intermediate dose (5 × 10 5 cells/kg) and the last three received the highest dose (1 × 10 6 cells/kg) of CD45RA − memory T cells. Clinicaltrials.gov registration: NCT04578210. Findings: All participants' clinical status measured by National Early Warning Score (NEWS) and 7-category point ordinal scales showed improvement six days after infusion. No serious adverse events were reported. Inflammatory parameters were stabilised post-infusion and the participants showed lymphocyte recovery two weeks after the procedure. Donor microchimerism was observed at least for three weeks after infusion in all patients. Interpretation: This study provides preliminary evidence supporting the idea that treatment of COVID-19 patients with moderate/severe symptoms using convalescent CD45RA − memory T cells is feasible and safe. Funding: Clinical Trial supported by Spanish Clinical Research Network PT17/0017/0013. Co-funded by European Regional Development Fund/European Social Fund. CRIS CANCER Foundation Grant to AP-M and Agencia Valenciana de Innovación Grant AVI-GVA COVID-19-68 to BS.